2011
DOI: 10.1111/j.1443-1661.2011.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of depressed‐type early gastric cancer using small‐caliber endoscopy with flexible spectral imaging color enhancement

Abstract: Small-caliber endoscopy with the FICE system provides better color contrast of depressed-type early gastric cancers than conventional small-caliber endoscopy, and the FICE system may facilitate the diagnosis of this type of cancer as a new endoscopic modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…204 To facilitate early detection, high-resolution endoscopy equipped with image-enhanced modalities such as narrow band imaging (NBI), flexible spectral imaging colour enhancement and blue laser imaging (BLI) have recently been introduced into clinical practice in Japan. [205][206][207] As better performance of image-enhanced endoscopy (IEE) has been documented, not only for detecting early gastric cancer, but also for Barrett's lesions, adoption of IEE for routine upper GI endoscopic examination is now highly recommended. This facilitates early detection of gastric cancer, which can be curable in the early stages (figure 9) with minimally invasive therapy.…”
Section: Gastric Cancermentioning
confidence: 99%
“…204 To facilitate early detection, high-resolution endoscopy equipped with image-enhanced modalities such as narrow band imaging (NBI), flexible spectral imaging colour enhancement and blue laser imaging (BLI) have recently been introduced into clinical practice in Japan. [205][206][207] As better performance of image-enhanced endoscopy (IEE) has been documented, not only for detecting early gastric cancer, but also for Barrett's lesions, adoption of IEE for routine upper GI endoscopic examination is now highly recommended. This facilitates early detection of gastric cancer, which can be curable in the early stages (figure 9) with minimally invasive therapy.…”
Section: Gastric Cancermentioning
confidence: 99%
“…However, it is often difficult to detect gastric superficial adenocarcinomas using conventional endoscopy with white-light imaging (C-WLI). Many clinical studies have reported on the diagnostic performance of EGC by imageenhanced endoscopy (IEE) techniques such as narrow-band imaging (NBI) [2][3][4][5][6][7][8][9] or flexible spectral imaging color enhancement (FICE) [10][11][12]. In particular, magnifying endoscopy with NBI (M-NBI) is a powerful optical IEE that has demonstrated accurate real-time diagnostic performance in EGC compared with C-WLI [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is often difficult to diagnose superficial EGC using C-WLI. Image-enhanced endoscopy techniques such as narrow-band imaging (NBI) [1], autofluorescence imaging [2], flexible spectral imaging color enhancement [3,4,5], and i-scan [6] have found wide applications for endoscopic diagnosis of EGC. In particular, magnifying NBI (M-NBI) is reportedly superior to C-WLI for the accurate diagnosis of EGC [7,8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%